Penggunaan Fermentasi Pakan Komplet Berbasis Hijauan Pakan dan Jerami Untuk Pakan Ruminansia - Bambang Suwignyo; Ali Agus; Ristianto Utomo; Nafiatul Umami; Bambang Suhartanto; Cahyo Wulandari (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2016)
Fermented complete feed (CF) based forage-fodder and agricultural by product as feed for ruminants can be implemented in the household and industrial purpose. Complete feed technology is one of alternative to solve the problems of stock and quality of feed. The nutritional value can be set by determine the number and type of mixture, livestock will not has an opportunity to choose so that it can minimize residual feed, practical, and can be stored for long periods. Fermented complete feed very much match to be implemented in the dry season or in the emergency situation. During Merapi Volcano eruption in 2010 was one of moment which is need CF technology. Rice straw can used for CF that can be socked during dry season, also the quality might improve (from 3—4% of crude protein content became 7—8%) with addition of rice brand or other ingredients. Fermented complete feed based on rice straw, forage-fodder or agricultural by product has a multifungtion in the emergency situation, reduce disaster risk, and feed security conservation.